Tanzania : Towards a Trade and Competitiveness Strategy to Propel Growth - World Bank (Washington, DC, 2014)
This policy note concerns to delineate the key components of a trade and competitiveness strategy for Tanzania. The objective is to provide a strategic framework and direction that would allow the country to exploit opportunities from the evolving trends in the global economy. The note is intended as an input to the Government of Tanzania's ongoing initiatives to enhance implementation of the national trade policy. Tanzania has an elaborate national trade policy (2003). Furthermore, the Government has recently taken an important step (in June 2007) by approving the Diagnostic Trade Integration Study (DTIS) to indicate willingness to implement its recommendations for addressing the constraints limiting Tanzania's integration in the global economy. Progress is been made to prepare implementation program. However, a clear strategy tightly linked to the new realities of international trade for guiding implementation is not yet in place. The motivation underlying this note is to provide a top down view of the strategic direction for guiding implementation of the policy and the various trade initiatives. The note is structure into four sections. Following this introduction, section two sets out the background and context within which the elements of the strategy are drawn. Section three delineates the key elements of the strategy and proposes strategic priorities for their implementation. Finally, section four identifies possible areas of further support by the World Bank through its technical assistance and analytical work in collaboration with other development partners.